2021
DOI: 10.3389/fanim.2021.767034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytogenic Feed Additive on Performance of Feedlot Cattle

Abstract: This study evaluated the influence of a blended phytogenic feed additive on feed intake, feeding behavior, nutrient digestibility, and growth performance during feedlot adaptation, early, and late finishing periods as well as carcass traits. Twenty-six crossbred F1 Angus × Nellore bulls (19 mo ± 4 d) were housed in individually pens and fed a high-forage receiving diet for 7 days. At the end of the receiving period, bulls were weighted [initial shrunk body weight (SBW) 363 ± 20 kg], blocked by SBW and randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This finding could be comparable to Borneman et al [ 49 ] demonstrated that the phenolic compound (vanillin) did not affect the in vitro DM digestibility of cellulose. Piran Filho et al [ 23 ] also reported that feeding aromatic compounds such as licorice, caraway, cinnamon, and vanilla to Angus Nellore cross bulls did not affect the apparent total tract digestibility parameters. Furthermore, Karimov et al [ 50 ] demonstrate that vanillin combined with probiotic strains ( Bifidobacterium longum and Bifidobacterium adolescentis / Lactobacillus acidophilus ) increases wheat digestibility, possibly due to changes in the rumen microbiome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could be comparable to Borneman et al [ 49 ] demonstrated that the phenolic compound (vanillin) did not affect the in vitro DM digestibility of cellulose. Piran Filho et al [ 23 ] also reported that feeding aromatic compounds such as licorice, caraway, cinnamon, and vanilla to Angus Nellore cross bulls did not affect the apparent total tract digestibility parameters. Furthermore, Karimov et al [ 50 ] demonstrate that vanillin combined with probiotic strains ( Bifidobacterium longum and Bifidobacterium adolescentis / Lactobacillus acidophilus ) increases wheat digestibility, possibly due to changes in the rumen microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that adding flavoring agents can improve feed acceptance [ 23 26 ]. However, there have been limited investigations that have examined the influence of flavoring compounds added to FCPU offered to grow beef on digestion, ruminal fermentation characteristics, and blood metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is substantial public and regulatory pressure to reduce overall antibiotic use to curtail proliferation of antibiotic resistant bacteria. As such, other methods are being explored to prevent LA formation in cattle, including vaccination [9], dietary supplementation with phytogenic additives (e.g., essential oils) [10, 11] or Saccharomyces cerevisiae fermentation products [12]. However, such approaches have only proven effective in vitro or under strictly controlled conditions and have not been widely adopted within the cattle industry [13, 14].…”
Section: Introductionmentioning
confidence: 99%